Differential Bacteriostatic Effects of Sucralose on Various Species of Environmental Bacteria. (30th September 2013) - Omran, Arthur; Baker, Ronald; Coughlin, Charles
Abstract : Sucralose was developed as a low-cost artificial sweetener that is nonmetabolizable and can withstand changes in pH and temperature. It is not degraded by the wastewater treatment process and thus has been found in waste water, estuaries, rivers and the Gulf Stream. Since the molecule can withstand heat, acidification, and microbial degradation, it is accumulating in the environment. The highest concentration of environmental sucralose detected to date is 300 ng/L. Our lab has isolated six bacterial species from areas that have been exposed to sucralose. We then cultured these isolates in the presence of sucralose looking for potential sucralose metabolism or growth acceleration. Instead we found something very interesting, bacteriostatic effects exhibited on all six isolates. This inhibition was directly proportional to the concentration of sucralose exposure. The efficiency of the growth inhibition seemed to be species specific, with various concentrations inhibiting each organism differently.